UVC (254 nm) and Far UVC (222 nm) Irradiation Affects In Vitro Growth of Colletotrichum sp. Isolates and Their Infection of Detached Strawberry Leaves - Barbara J. Smith; Blair J. Sampson; Warren E. Copes; Fumiomi Takeda; Wojciech J. Janisiewicz; Eric T. Stafne; Hamidou F. Sakhanokho; Jennifer B. Carroll (PhytoFrontiers)
Conventional ultraviolet C at 254 nm (UVC) and Far UVC at 222 nm (Far UVC) were evaluated as alternatives to fungicides for disease control. Conidia of 13 isolates of strawberry anthracnose pathogens (five Colletotrichum species in two complexes: C. acutatum and C. gloeosporioides) were uniformly dispersed onto agar and irradiated with UVC and Far UVC doses ranging from 52 to 1,248 J·m−2. After 48 h of incubation, a UVC dose of 1,248 J·m−2 and Far UVC doses from 234 to 935 J·m−2 reduced Colletotrichum colony counts to <10 colonies/Petri dish. Cultures exposed to UVC light followed by 4 h of darkness had lower colony counts than cultures incubated under continuous light. This dark incubation period was not required for Far UVC to obtain optimal lethality, indicating Far UVC irradiation can be applied during the day or night and achieve similar fungal lethality. Inoculation of detached leaves of three anthracnose-susceptible strawberry cultivars with conidial suspensions of Colletotrichum spp. revealed that UV irradiation can affect development of anthracnose symptoms. Leaves receiving UVC doses of 312 and 624 J·m−2 or a Far UVC dose of 467 J·m−2 reduced anthracnose infection with little or no plant injury. A UVC dose of 1,248 J·m−2 and Far UVC doses ≥ 467 J·m−2 inflicted varying degrees of plant injury. Disease control intended to reduce the number of fungicidal applications could be developed with moderate doses of UVC and Far UVC irradiation while slowing the evolution of pesticide-resistant strains. [Figure: see text] The author(s) have dedicated the work to the public domain under the Creative Commons CC0 “No Rights Reserved” license by waiving all of his or her rights to the work worldwide under copyright law, including all related and neighboring rights, to the extent allowed by law, 2024.